Online cognitive–behavioural therapy for traumatically bereaved people: study protocol for a randomised waitlist-controlled trial. Issue 9 (3rd September 2020) - Lenferink, Lonneke; de Keijser, Jos; Eisma, Maarten; Smid, Geert; Boelen, Paul
Abstract : Introduction: The traumatic death of a loved one, such as death due to a traffic accident, can precipitate persistent complex bereavement disorder (PCBD) and comorbid post-traumatic stress disorder (PTSD) and depression. Waitlist-controlled trials have shown that grief-specific cognitive–behavioural therapy (CBT) is an effective treatment for such mental health problems. This is the first study that will examine the effectiveness of online CBT (vs waitlist controls) in a sample exclusively comprised of people bereaved by a traumatic death. Our primary hypothesis is that people allocated to the online CBT condition will show larger reductions in PCBD, PTSD and depression symptom levels at post-treatment than people allocated to a waitlist. We further expect that reductions in symptom levels during treatment are associated with reductions of negative cognitions and avoidance behaviours and the experience of fewer accident-related stressors. Moreover, the effect of the quality of the therapeutic alliance on treatment effects and drop-out rates will be explored. Methods and analysis: A two-arm (online CBT vs waiting list) open-label parallel randomised controlled trial will be conducted. Participants will complete questionnaires at pretreatment and 12 and 20 weeks after study enrolment. Eligible for participation are Dutch adults who lost a loved one at least 1 year earlier due to a traffic accident and report clinically relevant levels of PCBD, PTSD and/or depression. Multilevel modelling will be used. Ethics and dissemination: Ethics approval has been received by the Medical Ethics Review Board of the University Medical Center Groningen (METc UMCG: M20.252121). This study will provide new insights in the effectiveness of online CBT for traumatically bereaved people. If the treatment is demonstrated to be effective, it will be made publicly accessible. Findings will be disseminated among lay people (eg, through newsletters and media performances), our collaborators (eg, through presentations at support organisations), and clinicians and researchers (eg, through conference presentations and scientific journal articles). Trial registration number: NL7497.